Given (A - 1) (B - 1) = AB - A - B + 1
I know the value for AB and the value for B - A
I need to manipulate this formula into having B - A in order to solve it.
Can anyone help? I don't even know if this is possible, and I think its the only step I need left to solve a problem.
The variables are:
Given (A - 1) (B - 1) = AB - A - B + 1
AB = 13407807929942597099574024998205846127479365820592 39337772356144372176407019990599692295402786034543 06307220698429599969155036639174988168806337957045 57141
B - A = 99756
Calculate the value for A and the value for B